2011
DOI: 10.1007/s00382-011-1092-3
|View full text |Cite
|
Sign up to set email alerts
|

Why does the Antarctic Peninsula Warm in climate simulations?

Abstract: The Antarctic Peninsula has warmed significantly since the 1950s. This pronounced and isolated warming trend is collectively captured by 29 twentiethcentury climate hindcasts participating in the version 3 Coupled Model Intercomparison Project. To understand the factors driving warming trends in the hindcasts, we examine trends in Peninsula region's atmospheric heat budget in every simulation. We find that atmospheric latent heat release increases in nearly all hindcasts. These increases are generally anthropo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
(52 reference statements)
1
3
0
Order By: Relevance
“…The trends range from + 0.22 (O'Higgins) to + 0.72 °C per 10 year (Rothera). Warming dominates from January to August, in agreement with previous results (Jacka and Budd, ; Steig et al , ; Qu et al , ). It is hardly perceptible in spring (from September to December), confirming once again Jacka and Budd ().…”
Section: Analysis Of Temperature Trendssupporting
confidence: 92%
See 1 more Smart Citation
“…The trends range from + 0.22 (O'Higgins) to + 0.72 °C per 10 year (Rothera). Warming dominates from January to August, in agreement with previous results (Jacka and Budd, ; Steig et al , ; Qu et al , ). It is hardly perceptible in spring (from September to December), confirming once again Jacka and Budd ().…”
Section: Analysis Of Temperature Trendssupporting
confidence: 92%
“…Gillett et al () and Monaghan and Bromwich () found that such observed changes in Antarctic temperature are not consistent with internal climate variability or natural climate drivers alone, and are directly attributable to human influence. More recently, Qu et al () highlight how the anthropogenic intensification of global hydrological cycle induces a strong increase of the latent heat transport into the Antarctic Peninsula, which explains the main part of the significant warming observed in this region through the 20th century. Polvani et al () suggest that most Southern Hemisphere tropospheric circulation changes, in austral summer and over the second half of the 20th century, have been caused by polar stratospheric ozone depletion.…”
Section: Introductionmentioning
confidence: 99%
“…6b), and cluster persistence (Fig. This is likely not so clear for generalized warm and cold days, such as depicted by clusters A and D. Their identification as recurrent regimes is likely due to the strong warming trend recorded over the region during the twentieth century (Qu et al 2012; section 3c), that attracted a large fraction of the overall Z 700 variance. 6d).…”
Section: B Twentieth-century Reanalysesmentioning
confidence: 96%
“…The rate and tendencies of warming at the Antarctic Peninsula are still subject of debate (Vaughan et al 2003;Martazinova et al 2010;Stastna 2010;Qu et al 2011;Schneider et al 2012;Bromwich et al 2013, Ding, Steig 2013Franzke 2013;Tymofeyev 2013;Turner et al 2016;Gonzalez, Fortuny 2018;Sato et al 2021), and the peninsula presents physical and geographical features that distinguish it from the rest of Antarctica (King, Tuner 1997;Vaughan et al 2003). The rugged alpine topography, a maritime climate along the west and central costa, and a continental climate along the east coast result in higher temperatures at the west coast compared to areas with similar latitudes and elevations on the east coast (Morris, Vaughan 1994).…”
Section: Introductionmentioning
confidence: 99%